Vibroacoustic behavior of a partially immersed cylindrical shell under point-force excitation: Analysis and experiment. (April 2020) - Zhao, Kaiqi; Fan, Jun; Wang, Bin; Tang, Weilin
Highlights: Vibroacoustic behavior of a partially immersed cylindrical shell is studied theoretically and experimentally. Sound radiation mechanism is analyzed using the dispersion characteristics of elastic wave on the shell. Oblique bright lines and weak interference fringes can be observed in the FDSs of sound pressure. Simple formulas are given to predict the bright resonance lines and weak interference fringes. Abstract: The vibroacoustic behavior of a partially immersed cylindrical shell under point–force excitation is studied using theoretical and experimental approaches. An analytical form of the vibroacoustic coupling equation is developed using a discretization approach for the circumferential angle along the shell's wet surface. The radiated sound and radial velocities are analyzed using frequency–depth spectra, and a series of regular oblique bright lines and weak interference fringes can be observed. For a partially immersed cylindrical shell, the subsonic flexural wave a 0 can radiate energy into the fluid from air-fluid demarcation points on the shell surface, and produce a series of resonant bright lines in the pressure spectra when the shell resonates in the circumferential direction. Interaction between the radiated waves, which propagate on parts of shell above and below the free surface (on the "dry part" and "wet part", respectively), produces interference fringes in the frequency–depth spectra of sound pressure. Furthermore, simple formulas are given to predict the lines and fringes using the phase velocities of a 0 wave on the dry and wet parts of the shell. Finally, experimental verification is carried out, and the measured frequency–depth spectra of the surface velocity and the sound pressure are consistent with the theoretical results.